2014
DOI: 10.4103/2141-9248.141542
|View full text |Cite
|
Sign up to set email alerts
|

Lipid profile and high maternal body mass index is associated with preeclampsia: A case-control study of the Cape Coast Metropolis

Abstract: Background:Preeclampsia is a leading cause of maternal mortality worldwide and a serious health problem that affects the majority of women.Aim:We investigated the association between lipid profile and maternal obesity among preeclamptic women in the Cape Coast Metropolis.Subject and Methods:This case–control study involved 60 preeclamptics and 50 healthy pregnant controls matched for age and gestational weeks consecutively recruited from two major hospitals in the Cape Coast Metropolis. Blood samples were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
21
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 16 publications
7
21
1
Order By: Relevance
“…Twenty‐seven studies reported on HDL levels,32, 37, 41, 44, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74 of which 24 studies could be included in a meta‐analysis 32, 37, 41, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72. HDL level was lower in pre‐eclampsia than in controls (mean difference −6.29 mmol/L; 95%CI −9.74−2.85; P  = 0.0003) with the strongest effect in subgroup analysis for severe pre‐eclampsia vs. controls ( Figure 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty‐seven studies reported on HDL levels,32, 37, 41, 44, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74 of which 24 studies could be included in a meta‐analysis 32, 37, 41, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72. HDL level was lower in pre‐eclampsia than in controls (mean difference −6.29 mmol/L; 95%CI −9.74−2.85; P  = 0.0003) with the strongest effect in subgroup analysis for severe pre‐eclampsia vs. controls ( Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-seven studies reported on HDL levels, 32,37,41,44, of which 24 studies could be included in a metaanalysis. 32,37,41,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] HDL level was lower in pre-eclampsia than in controls (mean difference À6.29 mmol/L; 95%CI À9.74À2.85; P = 0.0003) with the strongest effect in subgroup analysis for severe pre-eclampsia vs. controls (Figure 4).…”
Section: High-density Lipoproteinmentioning
confidence: 99%
“…PE is highly associated with hypertension both prior to and following pregnancy 12,13 . Other cardiovascular risk factors including increased levels of total cholesterol, LDL-C, and triglycerides and decreased levels of HDL-C have also been associated with PE 24,41 . The increased long-term risk of cardiovascular disease in women with prior PE includes an increased risk of CAD, ischemic stroke, heart failure, cardiac procedures, and cardiovascular-related hospitalizations [26][27][28][29]42,43 .…”
Section: Identification Of Traits and Their Associated Single Nucleotmentioning
confidence: 99%
“…VLDL transports TG in peripheral blood therefore hyper triglyceridemia also leads to increased serum levels of VLDL [28]. Insulin resistance causes lipolysis, leading to increased flux of fatty acids to liver promoting synthesis of VLDL [29].…”
Section: Original Research Articlementioning
confidence: 99%